2014
DOI: 10.3892/ijmm.2014.1801
|View full text |Cite
|
Sign up to set email alerts
|

Bushen-Yizhi formula ameliorates cognition deficits and attenuates oxidative stress-related neuronal apoptosis in scopolamine-induced senescence in mice

Abstract: Bushen-Yizhi formula (BSYZ), a traditional Chinese medicine formula consisting of six herbs has been reported to possess a neuroprotective effect. The present study aimed to investigate the effects of BSYZ on learning and memory abilities, as well as oxidative stress and neuronal apoptosis in the hippocampus of scopolamine (SCOP)-induced senescence in mice, in order to reveal whether BSYZ is a potential therapeutic agent for Alzheimer’s disease (AD). A high-performance liquid chromatography (HPLC) fingerprint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
2
35
0
2
Order By: Relevance
“…A previous study demonstrated that continuous intracisternal infusion of Aβ 1-40 in rats resulted in significantly decreased protein expressions of Mn-SOD, GSH, glutathione disulfide (GSSG) in the rat brain, suggesting that Aβ 1-40 impairs anti-oxidant capacity (Tsai et al, 2010). Another study showed that SCOP-induced changes in reactive oxygen species (ROS), malondialdehyde (MDA), and AChE activity in mice (Hou et al, 2014;Lee et al, 2014). Data show that intracisternal injection of Aβ 1-40 infusion for 14 days decreased Mn-SOD expression and increased Cu, Zn-SOD activity.…”
Section: Ferulic Acid Reverses the Cognitive Dysfunctionmentioning
confidence: 99%
“…A previous study demonstrated that continuous intracisternal infusion of Aβ 1-40 in rats resulted in significantly decreased protein expressions of Mn-SOD, GSH, glutathione disulfide (GSSG) in the rat brain, suggesting that Aβ 1-40 impairs anti-oxidant capacity (Tsai et al, 2010). Another study showed that SCOP-induced changes in reactive oxygen species (ROS), malondialdehyde (MDA), and AChE activity in mice (Hou et al, 2014;Lee et al, 2014). Data show that intracisternal injection of Aβ 1-40 infusion for 14 days decreased Mn-SOD expression and increased Cu, Zn-SOD activity.…”
Section: Ferulic Acid Reverses the Cognitive Dysfunctionmentioning
confidence: 99%
“…MDA, HNE, or TBARS were enhanced in all of those models in the cerebral cortex or/and hippocampus or/and the whole brain [237][238][239][240][241][247][248][249][250][251][252][253][254][255]. Oxidative modification of proteins has also been demonstrated in the cortex and whole brain homogenate of transgenic AD mice [253,255] and in the cerebral cortex and hippocampus of an Aβ 1-42 mouse model [247].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Diminished levels of GSH in the cerebral cortex or hippocampus or in whole brain lysates have been demonstrated in pharmacologically induced AD animal models [237,238,240,241,247,250,254,256].…”
Section: Antioxidant Defense Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations